Mean Platelet Volume and Size Distribution and Their Sensitivity to Agonists in Patients with Coronary Artery Disease and Congestive Heart Failure - Erne, P; Wardle, J; Sanders, K; Lewis, S M; Maseri, A (Thrombosis and Haemostasis, 1988)
Mean platelet volume was related to platelet count in patients with myocardial infarction (n = 55) and patients with congestive heart failure (n = 9). 18 patients with acute myocardial infarction were tested at admission and 4-7 days later, together with 13 patients with chronic stable angina and 10 patients with chest pain which was not related to coronary artery disease. In citrated blood a relative reduced frequency of large platelets (>13 fl) occured in patients with acute myocardial infarction at admission but was not seen during recovery or in patients with chronic stable angina. This suggests consumption of large platelets at time of thrombus formation. No relation was found between plasma catecholamine levels and mean platelet volumes. Effects of serotonine, adrenaline and CGP 28392, a calcium agonist, on platelet volume distributions were determined. Sensitivity of platelets to adrenaline was increased in patients with acute myocardial infarction on admission and reduced 4-7 days later, while in patients with congestive heart failure reactivity to both serotonine and adrenaline were reduced. This indicates a fast down-regulation during the early recovery phase of myocardial infarction and chronically in congestive heart failure.
Keywords: Mean platelet volume; Platelet volume distribution; Coronary artery disease; Congestive heart failure; Serotonine; Adrenaline; CGP 28392